"In the Bengali Vocabulary, There Is No Such Word as Care Home": Caring Experiences of UK Bangladeshi and Indian Family Carers of People Living With Dementia at Home. (6th October 2019) - Herat-Gunaratne, Ruminda; Cooper, Claudia; Mukadam, Naaheed; Rapaport, Penny; Leverton, Monica; Higgs, Paul; Samus, Quincy; Burton, Alexandra
Abstract: Background and Objectives: We aimed to explore experiences of South Asian carers of people with dementia receiving health or social care in the United Kingdom, purposively recruited to encompass a range of migration, economic and cultural experiences. While previous work in this area has reported carers' understanding of, and attitudes to dementia, we explored how carers' cultural identities and values influenced their experiences, negotiation of the caring role and relationship with services. Research Design and Methods: We conducted semi-structured interviews with 10 Bangladeshi and Indian family carers of people living with dementia at home. We recruited participants from community settings in London and Bradford, UK. Interviews were audio recorded, transcribed and thematically analyzed. Results: We identified 4 themes: an expectation and duty to care, expectation and duty as a barrier to accessing formal care (family carer reluctance, care recipient reluctance, and service organization), culturally (in)sensitive care, and the importance of support from informal care networks. Discussion and Implications: Interviewees described tensions between generations with different understandings of familial care obligations. Expectations to manage led to burden and guilt, and the cost of caring, in terms of lost employment and relationships was striking. Unlike in previous studies, interviewees wanted to engage and be supported by services, but were frequently offered care models they could not accept. There was a tension between a state-provided care system obliged to provide care when there are no alternatives, and family carers who feel a duty to always provide alternatives. Informal social networks often provided valued support.